Plastid‐mediated singlet oxygen in regulated cell death. (17th May 2021) - Bhatt, M.; Pandey, S. S.; Tiwari, A. K.; Tiwari, B. S.
Abstract: Reactive oxygen species (ROS) generation within a cell is a natural process of specific subcellular components involved in redox reactions. Within a plant cell, chloroplasts are one of the major sources of ROS generation. Plastid‐generated ROS molecules include singlet oxygen ( 1 O2 ), superoxide radical (O2 – ), hydroxyl radical (OH ) and hydrogen peroxide (H2 O2 ), which are produced mainly during photochemical reactions of photosynthesis and chlorophyll biosynthetic process. Under normal growth and developmental, generated ROS molecules act as a secondary messenger controlling several metabolic reactions; however, perturbed environmental conditions lead to multi‐fold amplification of cellular ROS that eventually kill the target cell. To maintain homeostasis between production and scavenging of ROS, the cell has instituted several enzymatic and non‐enzymatic antioxidant machineries to maintain ROS at a physiological level. Among chloroplastic ROS molecules, excess generation of singlet oxygen ( 1 O2 ) is highly deleterious to the cell metabolic functions and survival. Interestingly, within cellular antioxidant machinery, enzymes involved in detoxification of 1 O2 are lacking. Recent studies suggest that under optimal concentrations, 1 O2 acts as a signalling molecule and drives the cell to either the acclimation pathway or regulated cell death (RCD). Stress‐induced RCD is a survival mechanism for the whole plant, while the involvement of chloroplasts and chloroplast‐localized molecules that execute RCD are not well understood. In this review, we advocate for participation of chloroplasts‐generated 1 O2 in signalling and RCD in plants. Abstract : Chloroplast‐ mediated generation of singlet oxygen plays a pivotal role in abiotic stress‐ induced regulated cell death